The Relationship Between Teacher Teaching Variations and the Learning Environment With Student Learning Outcomes at SMPN 16 Padang - Darmisal Darmisal; Buchari Nurdin (International Journal of Educational Dynamics, 2020)
This research is motivated by the teacher's teaching ability that does not vary and the conditions of the learning environment that is less supportive of causing a decrease in student learning outcomes, in Social Sciences subjects. The purpose of this study is to analyze the relationship 1) Variations in teaching teachers with student social learning outcomes. 2) Learning environment with students' social studies learning outcomes. 3) Variations in teacher teaching and learning environment together with students' social studies learning outcomes. This research is a quantitative descriptive correlational study. The population of this study was 789 students while the study sample was taken based on the Proportional Startified Random Sampling technique obtained a sample of 88 people, data collection using questionnaire interval processing scores using data processing applications SPSS. Based on the results of research analysis on the Relationship of Teacher Teaching Variations and Learning Environment Against Social Studies Learning Outcomes of Students at SMPN 16 Padang, the results show that 1) There is a significant relationship between teacher teaching variations and student social learning outcomes. 2) There is a significant relationship between the learning environment and students' social studies learning outcomes. 3) There is a significant relationship between variations in teacher teaching and the learning environment together with students' social studies learning outcomes. This research is recommended to social studies teachers to pay more attention to variations in learning and the learning environment so as to improve student learning outcomes.